Optimally combining censored and uncensored datasets - Paul J. Devereux; Gautam Tripathi (University College Dublin, UCD School of Economics, 2008)
We develop a simple semiparametric framework for combining censored and uncensored samples so that the resulting estimators are consistent, asymptotically normal, and use all information optimally. No nonparametric smoothing is required to implement our estimators. To illustrate our results in an empirical setting, we show how to estimate the effect of changes in compulsory schooling laws on age at first marriage, a variable that is censored for younger individuals. Results from a small simulation experiment suggest that the estimator proposed in this paper can work very well in finite samples.
hdl:10197/744
Keywords: 330